Traditional Knowledge and Fungal Characterization of Kotok Bongkok for the Development of Local Wisdom-Based Food Innovation - Sindanita Yulianty; Mila Ermila Hendriyani; Rida Oktorida Khastini; Mariska Sandrina Oktavianti; Putri Dian Pramesty (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2026)
Kotok Bongkok is a fermented local dish from Lebak Regency, Banten, using seeds of kluwek (Pangium edule) via fermentation method by boiling the seeds, peeling the seed skins, soaking in mountain spring water, and fermenting naturally in bamboo. This research attempts to study the local knowledge of communities on the process of making kotok bongkok and determine the type of fungi used during the fermentation process. The data were collected based on field observation, informal and semi-structured interview on 92 informants, as well as identifying the fungi characteristic by morphological and microscopic isolation. The findings reveal that women, especially teenagers age 15-17 years old, dominantly preserve the knowledge on how to make kotok bongkok. The fermentation process creates an exclusive taste and decreases cyanide considerably. Preliminary identification on microbiology analysis shows dominant fungi that exist during fermentation process are Mucor racemosus, Rhizopus oligosporus, and yeasts which create specific aroma on the product. Based on proximate analysis, this fermented product has high content of fat and moisture, followed by protein and fiber. This study emphasizes that Kotok Bongkok is a biocultural heritage that unites biological and cultural aspects, and it has the potential to be developed as an innovative food product based on local wisdom to support food security and green economy principles through community empowerment, and the preservation of Indonesia’s culinary identity.